1994
DOI: 10.1002/jctb.280610106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of lactose isomerisation to lactulose in an alkaline medium

Abstract: The aim of this work was to determine easily and quickly the operating conditions for the industrial production of lactulose (rate of isomerisation, rate of lactose degradation, reaction time, temperature, pH). The kinetic equations of lactulose formation and lactose degradation in an alkaline medium (NaOH) were determined. Experiments were carried out at different OH− concentrations (0·5 × 10−2–19 × 10−2 mol dm−3) and at different temperatures (328–353 K). A kinetic model is presented which can be used to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Apart from this, the transformation of lactose into lactulose through the chemical-based processes typically resulted to a quick degradation of lactulose into galactose and tagatose along with some other acidic byproducts including isosaccharinic and formic acids, ,, resulting in the dropping of pH in a feed medium. , In essence, in the conventional isomerization, the use of a high temperature in an alkaline medium triggers isomerization and degradation of lactose and lactulose into epilactose and galactose. , However, in this study, this phenomenon was not observed and, subsequently, only galactose was produced as a reaction byproduct.…”
Section: Resultsmentioning
confidence: 59%
“…Apart from this, the transformation of lactose into lactulose through the chemical-based processes typically resulted to a quick degradation of lactulose into galactose and tagatose along with some other acidic byproducts including isosaccharinic and formic acids, ,, resulting in the dropping of pH in a feed medium. , In essence, in the conventional isomerization, the use of a high temperature in an alkaline medium triggers isomerization and degradation of lactose and lactulose into epilactose and galactose. , However, in this study, this phenomenon was not observed and, subsequently, only galactose was produced as a reaction byproduct.…”
Section: Resultsmentioning
confidence: 59%
“…Besides calcium hydroxide, other catalysts that have been used are sodium hydroxide, potassium hydroxide, sodium carbonate (Harr & Pluim, 1991;Deya & Takahashi, 1991;Dendene et al, 1994;Zokaee et al, 2002), sodium sulfite (Gasparotti, 1981), sodium aluminate, magnesium oxide (Wang et al, 2017), boric acid (Hicks & Parrish, 1980;Hicks et al, 1984), and organic alkaline reagents, such as tertiary amines (Parrish, 1970;Dendene et al, 1994;Zokaee et al, 2002). However, these catalysts provide low yields because some undesirable products are also formed during the process (Hicks & Parrish, 1980;Mizota et al, 1987).…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Lactulose complexing reagents, e.g. sodium borate, minimize the secondary reactions, resulting in high yields of lactulose by shifting the equilibrium to favor lactulose formation, by its complexation with lactulose (Dendene et al, 1994;Zokaee et al, 2002).…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The large number of complex reagents such as aluminate and borate (Carobbi & Innocenti, 1990;Krumbbloz & Dorscheid, 1991;Zokaee et al, 2002), alkalies i.e. sodium hydroxide (De Haar & Plump, 1991;Deya & Takahashi, 1991;Dendene et al, 1994;Zokaee et al, 2002), magnesium oxide (Carobbi et al, 1985), tertiary amines (Parrish et al, 1980) have been used as a catalysts for the production of lactulose.…”
Section: Lactulosementioning
confidence: 98%